Evaluating the effectiveness of the SMART contract-signing strategy in reducing the growth of Swedish Adolescents' substance use and problem behaviors. (December 2016) - Bortes, Cristian; Geidne, Susanna; Eriksson, Charli
Abstract Background In 2013, around 40 % of the schools in Sweden had structured programs to prevent tobacco and alcohol debut in compulsory school. There has unfortunately been a lack of scientific evidence to support most of the prevention methods focusing on primary prevention in schools in Sweden. The aim and purpose of the present study is to evaluate the effectiveness of the Non-Governmental Organization SMART contract-signing strategy in reducing the growth of youth substance use and other problem behaviors amongst Swedish adolescents. Methods Students from five schools in a medium-sized Swedish municipality were surveyed in three waves from 7th to 9th grade of compulsory school. We used General Linear Model (GLM) repeated-measures ANOVA to test if the outcome measures smoking, use of snus and alcohol, drunkenness, delinquency, and bullying significantly changed different amounts over time in groups that had participated in the SMART program for long time, a short time, sporadically- or not at all. Groups were compared on demographic background variables, and outcome measures were assessed on all measurement occasions by a one-way ANOVA. The magnitude of group differences at the end of the study was estimated according to Cohen'sd . Results Number of years with a contract has an effect on the levels of self-reported youth problems in 9th grade. We found small to medium-sized differences in measured outcomes between students who participated in the program for the longest period of time, 5 years, and who participated for the shortest time, 0–2 years. Conclusion Findings suggests that the SMART program has preventive effects on adolescent substance use.